Intrathoracic Muscular Transposition in Chronic Tuberculous Empyema - Ahn, Hyo Yeong; Cho, Jeong Su; Kim, Yeong Dae; Hoseok, I. (The Thoracic and Cardiovascular Surgeon, 2013)
Background The effective management of chronic tuberculous empyema requires an evacuation of pus and a re-expansion of the lung or an obliteration of the empyema space such as closed thoracostomy, decortication, or open window thoracostomy (OWT) followed by intrathoracic muscular transposition (IMT). However, the most effective management of chronic tuberculous empyema is still debatable.Methods From June 1999 to July 2010, 18 patients with chronic tuberculous empyema who underwent OWT and/or IMT were enrolled in this study. The causes of empyema, and methods and outcomes of treatment were retrospectively reviewed. The success rate of IMT was investigated to evaluate the efficacy.Results Mean patient age was 54.3 ± 14.9 years and 16 patients were male. Depending on operative methods, three groups were divided: OWT only (n = 4); two-stage operation as OWT followed by IMT (n = 7); and one-stage operation as OWT with IMT simultaneously (n = 7). Of 14 patients who underwent IMT, 13 patients successfully recovered from empyema and bronchopleural fistula (BPF) (success rate, 92.86%), but one patient developed a secondary bacterial infection. There was no operative mortality.Conclusion This study suggests that IMT may be an effective option to control infection or BPF in chronic tuberculous empyema.
Keywords: tuberculosis; pleural disease (incl. drainage); chest wall